Conceptions of Teaching and Learning using Virtual Learning Environments: Preliminary Findings From a Phenomenographic Inquiry - Lameras, Petros; Paraskakis, Iraklis; Levy, Philippa (Proceedings of the International Conference on Networked Learning, 2008)
This paper reports a sub-set of findings from an in-depth study of Greek university teachers’ conceptions of, and approaches to, the use of virtual learning environments (VLEs) in teaching. A central strand of the study is an exploration of factors influencing the development of networked learning in Greek higher education (HE) through a qualitative examination of the pedagogical perspectives that teachers bring to bear on their use of new information and communication technologies (ICTs: in this case, specifically VLEs such as WebCT, Blackboard or Moodle). The project is investigating the relationship between Greek university teachers’ conceptions of teaching using VLEs and current theoretical perspectives of relevance to the e-learning field, in particular those perspectives that are associated with the principles and practices of networked learning as a distinctive form of e-learning. The paper presents preliminary findings from this strand in the light of previous research into teachers’ conceptions of teaching and use of VLEs. A phenomenographic research approach has been adopted for this study. Phenomenography is an interpretive approach that seeks to identify the range of variation in ways of perceiving or experiencing a phenomenon of interest in this case the way in which Greek university teachers understand the educational use of VLEs. For the pilot study, the sample included five computer science academics from three universities in Greece. The interviews concentrated on seeking variations in pedagogical purposes in using VLEs for teaching and learning, and in approaches to their use Analysis of the open-ended interviews revealed three qualitatively different conceptions of teaching using VLEs, and different pedagogical approaches associated with them. The ’information transfer’ conception was associated with information- (or content) - oriented pedagogical approaches to using VLEs. ’Understanding concepts’ and ’developing concepts’ conceptions were associated with more activity- (or process-) oriented approaches. The data suggest that there may be a relationship between the subject being taught (within the broad discipline of computer science) and different conceptions and approaches to using VLEs. Although based on a very small sample, the pilot study also suggests that pedagogical conceptions and approaches associated with networked learning may not be widely prevalent in computer science teaching in Greece